INTEGRASI DATA BASE BERBASIS CLOUD UNTUK SKALABILITAS BISNIS: STUDI KASUS NETFLIX - Tri Putri Rezeki; Muhammad Irwan Padli Nasution (JOURNAL SAINS STUDENT RESEARCH, 2025)
Cloud-based database integration is a strategic solution to the challenges of data management in the digital era. By combining a structured database system and flexible cloud computing technology, companies can improve operational efficiency, system scalability, and data security. This paper discusses the basic concepts of databases and cloud computing, cloud service models (IaaS, PaaS, SaaS), the main benefits of cloud-based database integration, and a case study of its implementation at Netflix. The results of the discussion show that this integration provides various advantages, such as cost efficiency, high data accessibility, fast disaster recovery, and ease of collaboration and decision making. The Netflix case study reinforces the finding that cloud databases are able to support sustainable global business growth.